IN VITRO ANTITUBERCULOUS ACTIVITY OF THYMOQUINONE, AN ACTIVE PRINCIPLE OF NIGELLA SATIVA - Randhawa, Muhammad Akram (Journal of Ayub Medical College Abbottabad, 2011)
Background: Nigella sativa seed has been used in folk medicine against many ailments including infections. The present study was aimed to investigate activity of thymoquinone, in vitro, against clinical isolates of Mycobacterium tuberculosis. Methods: Mycobacteria obtained from patients of King Fahd Hospital of University, Alkhobar, Saudi Arabia were subcultured at 37 °C in MGIT tubes containing Middlebrook broth and OADC growth supplement and growth detected by BACTEC MicroMGIT fluorometer on day 10. Mycobacteria were then inoculated in MGIT tubes containing thymoquinone 2.5, 5, 10, 20, 40, 80 ïg/ml, streptomycin 1.25 ïg/ml or controls in Middlebrook broth plus supplement, incubated at 37 °C for 14 days and read daily for fluorescence. In addition, isolates were inoculated in culture tubes containing Middlebrook agar (plus supplement) in presence of thymoquinone 2.5, 5, 10, 20, 40, 80 ïg/ml, streptomycin 1.25 ïg/ml or controls, and incubated at 37 °C for 4 weeks. Results: In Middlebrook broth, fluorescence test for tuberculosis was negative with thymoquinone 20, 40 and 80 ïg/ml and streptomycin 1.25 ïg/ml up to day 14th. With controls, thymoquinone 2.5, 5 and 10 ïg/ml fluorescence was detectable from day 10 to 14. In Middlebrook agar, there was no visible growth of tubercle bacillus with thymoquinone 20, 40 and 80 ïg/ml and streptomycin 1.25 ïg/ml, however, with controls, thymoquinone 2.5 and 5 ïg/ml abundant and with 10 ïg/ml few colonies were observed. Conclusions: Thymoquinone possesses activity against M. tuberculosis with MIC of 20 ïg/ml and has potential for further investigation. Our study confirms the benefit of N. sativa in native medicine against chest infection. Keywords: Nigella sativa, thymoquinone, Mycobacterium tuberculosis, Micro MGIT fluorometer, Middlebrook broth, Middlebrook agar